2020
DOI: 10.1021/acs.iecr.9b06349
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Conversion of Xylose to Furfural in a Water–MIBK System Catalyzed by Magnetic Carbon-Based Solid Acid

Abstract: In this work, the conversion of xylose to furfural (FF) was effectively achieved in a water-MIBK biphasic solvent system over the synthesized magnetic carbon-based solid acid catalyst (MMCSA). The effect of various reaction conditions was studied on the dehydration of xylose and the highest FF yield of 79.04% was obtained.Byproducts in the reaction process were identified by high-performance liquid chromatography-mass spectrometry (LC-MS), which provides insights into the reaction pathway of the xylose convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The results reveal that the S content dramatically decreased from that of fresh catalyst. This suggests that the decline in FF yield was caused by loss of the SO 3 H acid sites during repeated runs [49,[54][55][56]. The FF yield decrease has been observed in prior studies on FF production from xylose catalysed by an SO 3 H solid catalyst [23,55,57,58].…”
Section: (D) Catalytic Activity In Dehydration Reaction Of Xylose To Furfuralmentioning
confidence: 57%
See 1 more Smart Citation
“…The results reveal that the S content dramatically decreased from that of fresh catalyst. This suggests that the decline in FF yield was caused by loss of the SO 3 H acid sites during repeated runs [49,[54][55][56]. The FF yield decrease has been observed in prior studies on FF production from xylose catalysed by an SO 3 H solid catalyst [23,55,57,58].…”
Section: (D) Catalytic Activity In Dehydration Reaction Of Xylose To Furfuralmentioning
confidence: 57%
“…This suggests that the decline in FF yield was caused by loss of the SO 3 H acid sites during repeated runs [49,[54][55][56]. The FF yield decrease has been observed in prior studies on FF production from xylose catalysed by an SO 3 H solid catalyst [23,55,57,58]. Although after the fifth run the FF yield had clearly degraded, the catalyst could still be easily separated with a magnet (electronic supplementary material, figure S2).…”
Section: (E) Reusability Study Of So 3 H@fe/mc Catalystmentioning
confidence: 58%
“…It was noted that the maximum conversion and yield were obtained at 160 • C, but the reaction temperature was above 160 • C and furfural yield decreased. The decrease in yield at 160 • C indicated that side reaction rates increased more than that of furfural formation [24]. Subsequently, temperature (160 • C) and time (120 min) were used as reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…was used to hydrolyze xylose to produce furfural under more severe hydrothermal condition (190 °C). The main reason why its reusability is difficult to guarantee is still the leaching of the −SO 3 H group, which acts as the catalytic active center [50] . The study of Lang et al.…”
Section: Resultsmentioning
confidence: 99%